1984
DOI: 10.1128/iai.46.2.324-331.1984
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytotoxic effects of toxins A and B isolated from Clostridium difficile

Abstract: Toxin A and toxin B preparations of Clostridium difficile have been shown to affect metabolic functions of intact HeLa cells with different kinetics. The cytotoxins were purified from dialyzed filtrates of C. difficile strain VPI 10463 by hydrophobic interaction chromatography and ion-exchange chromatography and were concentrated by dialysis or by ultrafiltration. The toxins, which are immunologically unrelated, were analyzed by polyacrylamide gel electrophoresis and by immunochemistry with the Western blot te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…These toxins are known to alter cell metabolism and inhibit protein synthesis. 27,28 In animal models, the individual toxins are capable of causing severe colitis, similar to that seen with CDAD. 11,13 Tolevamer apparently binds these toxins in the colon, thereby blocking their ability to interact effectively with the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These toxins are known to alter cell metabolism and inhibit protein synthesis. 27,28 In animal models, the individual toxins are capable of causing severe colitis, similar to that seen with CDAD. 11,13 Tolevamer apparently binds these toxins in the colon, thereby blocking their ability to interact effectively with the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The other toxin is cytotoxin or toxin B which shows cytotoxicity to the cultured cells. Many investigators (2,9,11,16,17,23,24,26) focused their study on enterotoxin to determine characteristics which might relate to causing diarrhea and other clinical features. They established the method of purification of enterotoxin and characterized its properties.…”
Section: Immunological Properties Of Purified Cytotoxinmentioning
confidence: 99%
“…It has been reported that this organism produced at least two kinds of toxin (2,4,17,21,(24)(25)(26) ; one is a toxin named toxin A or enterotoxin which induces an intestinal fluid accumulation in animal experiments (2,16,17,26), and the other is toxin B or cytotoxin which is cytotoxic on tissue cultured cells (2,16,20,24,26). Several investigators including us (2,9,11,23,24) have established the purification method of enterotoxin, and the importance of this toxin in the pathogenesis of C. difficile enteritis has been documented (18,26). Data on the cytotoxin reported up to now, however, are inconsistent.…”
mentioning
confidence: 98%
“…which are implicated in the pathogenesis of the colitis (10)(11)(12)(13)16). Enterotoxin A (EA) causes accumulation of fluid in ligated rabbit ileal loops (11,13), whereas cytotoxin B appears to have primarily a cytotoxic effect on tissue culture cells (12,17,20,28). The toxins have a complex effect on cultured cells and intestinal tissue, including changes in ionic balance and morphology of the cells (11,17,20).…”
mentioning
confidence: 99%